Clinical Characteristics of Patients with Glaucoma Presenting to Bharatpur Eye Hospital: An Observational Study - Sah, Ranjeet Kumar; Byanju, Raghunandan; Bhandari, Sangita Sharma; Shrestha Ligal, Anju; Bhandari, Gopal (Nepalese Journal of Ophthalmology, 2022)
Introduction: Glaucoma is the second leading cause of blindness worldwide. Glaucoma will affect 79.6 million individuals by 2020, according to projections. Improved glaucoma screening and treatment approaches are urgently needed. The purpose of this study is to determine the clinical characteristics of glaucoma patients who visit Bharatpur Eye Hospital and aims to calculate the number of new diagnoses of glaucoma from 01 February 2020 to 15 March 2020. Materials and methods: This is a hospital-based, cross-section study. All patients with a diagnosis of glaucoma were invited to participate. The examination findings, diagnosis, and management were all documented. A standardized questionnaire was used to collect patient knowledge and understanding of glaucoma.Results: Among 127 patients 52.8% were newly diagnosed with glaucoma. Many patients (59.8%) were symptomatic for more than 6 months. The mean presenting intraocular pressure was 20.86 mm Hg with an SD of 11.55 mm Hg. Only 44.9% of the participants had heard about glaucoma. Many participants (65.4%) did not have knowledge of glaucoma. Among 127 participants 9.4% had a family history of glaucoma.Conclusion: Glaucoma is a significant burden that presents challenges to ophthalmic services in Chitwan. Many people have a poor understanding of their condition and have limited access to services. There is a need to build a treatment infrastructure and raise public awareness.